The time of day in the descriptions of the deaths of russian saints in the XIV-XVI centuries - Donskoi Gleb (Вестник Православного Свято-Тихоновского гуманитарного университета: Серия ИИ. История, история Русской Православной Церкви)
In this paper we study point to the time of day in the descriptions of Russian saints deaths XIV-XVI centuries. The author tries to figure out what time of day, according to ancient hagiography, could be a sign of a righteous man’s death and was a comfort to grieving relatives at the deathbed of saint. The outcome of the study is the finding that the death during the daylight hours, dominating the lives of the saints, is a sign of salvation of the soul deceased person.